Case report: Nasal polyp exfoliated into the tracheal tube in a patient with a difficult airway during nasotracheal intubation - Bai, Fu-Rong; Zhang, Shuang; Yi, Ming-liang (Frontiers in Anesthesiology, 2022)
Background: Difficult airway has always been one of the greatest challenges for anesthesiologists. Patients with difficult airways and severe obstructive sleep apnea-hypopnea syndrome (OSAHS) often find themselves in life-threatening danger before their artificial airway is established and after their artificial airway is removed. Case Presentation: The study reported a case of nasal polyps shedding into the tracheal tube when nasotracheal intubation in a patient diagnosed with a difficult airway and OSAHS; the patient was being prepared for a transoral tonsillectomy under general anesthesia. The uniqueness of this case was that nasal polyps were scraped off using the tracheal tube during nasotracheal intubation, and detected in real-time; this ultimately prevented an airway foreign body obstruction. Reviewing the literature on intubation methods for difficult airways, awake endotracheal intubation guided by fiberoptic bronchoscopy remains to be the gold standard for airway management. Additionally, nasotracheal intubation can provide more operating space for oral surgery. In this case, the unexpected nasal polyp fell off into the tracheal tube during intubation, as is visualized on Figure 1. This fortunate event prevented the nasal polyp from falling into the trachea and bronchus. Conclusion: It is necessary to rule out any nasal abnormalities in patients requiring nasotracheal intubation; otherwise, blind nasal intubation may be dangerous.